Fruit extract of the medicinal plant Crataegus oxyacantha exerts genotoxic and mutagenic effects in cultured cells - de Quadros, Ana Paula Oliveira [UNESP]; Mazzeo, Dania Elisa Christofoletti [UNESP]; Marin-Morales, Maria Aparecida [UNESP]; Perazzo, Fábio Ferreira; Rosa, Paulo Cesar Pires; Maistro, Edson Luis [UNESP] (Taylor & Francis, 2017)
Crataegus oxyacantha, a plant of the Rosaceae family also known “English hawthorn, haw, maybush, or whitethorn,” has long been used for medicinal purposes such as digestive disorders, hyperlipidemia, dyspnea, inducing diuresis, and preventing kidney stones. However, the predominant use of this plant has been to treat cardiovascular disorders. Due to a lack of studies on the genotoxicity of C. oxyacantha, this investigation was undertaken to determine whether its fruit extract exerts cytotoxic, genotoxic, or clastogenic/aneugenic effects in leukocytes and HepG2 (liver hepatocellular carcinoma) cultured human cells, or mutagenic effects in TA100 and TA98 strains of Salmonella typhimurium bacterium. Genotoxicity analysis showed that the extract produced no marked genotoxic effects at concentrations of 2.5 or 5 µg/ml in either cell type; however, at concentrations of 10 µg/ml or higher significant DNA damage was detected. The micronucleus test also demonstrated that concentrations of 10 µg/ml or higher produced clastogenic/aneugenic responses. In the Ames test, the extract induced mutagenic effects in TA98 strain of S. typhimurium with metabolic activation at all tested concentrations (2.5 to 500 µg/ml). Data indicate that, under certain experimental conditions, the fruit extract of C. oxyacantha exerts genotoxic and clastogenic/aneugenic effects in cultured human cells, and with metabolism mutagenicity occurs in bacteria cells.